Cathode modification of polymer solar cells by ultrahydrophobic polyelectrolyte. (12th August 2016) - Shin, Woong; Sylvianti, Nadhila; Marsya, Mutia Anissa; Putri, Devi Saskia; Chang, Dong Wook; Kim, Ju-Hyung; Kim, Youn Whan; Kim, Tae-Dong; Yoo, Seong Il; Kim, Joo Hyun
ABSTRACT: A ultrahydrophobic polylectrolyte (PVPy-F) based on poly(4-vinylpyridine) is applied to polymer solar cell (PSC) as a cathode buffer layer. The Kelvin probe microscopy measurement support the formation of favorable interface dipole between the active layer and the cathode. PSC with the PVPy-F as a cathode buffer layer demonstrate the power conversion efficiency (PCE) of 3.46% (open circuit voltage (Voc ) = 0.62 V, short circuit current (Jsc ) = 10.8 mA/cm 2, fill factor (FF) = 51.7%), which is better than the device without interlayer (PCE = 2.88%, Voc = 0.61 V, Jsc = 9.15 mA/cm 2, FF = 51.6%). This is due to that the reduction of a Schottky barrier at the cathode interface. Most increase in the PCE of the devices with interlayer is resulted from enhancement of the Jsc .